Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0085467
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydrophilic Ionic Liquids 1-Ethyl-3-Methylimidazolium Lactate and Choline Lactate on Lipid Vesicle Fusion

Abstract: Ionic liquids (ILs) are room-temperature molten salts that have applications in both physical sciences and more recently in the purification of proteins and lipids, gene transfection and sample preparation for electron microscopy (EM) studies. Transfection of genes into cells requires membrane fusion between the cell membrane and the transfection reagent, thus, ILs may be induce a membrane fusion event. To clarify the behavior of ILs with cell membranes the effect of ILs on model membranes, i.e., liposomes, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…37 increased further, relatively higher amount of dye leaks out in the fusion time period and hence, relatively higher saturation values are observed. These amphiphilic cations have been shown to induce fusion in egg-PC 24 and DOPC vesicles 23 previously. However, these studies did not comment on the leaky nature of membrane fusion or formation of fusion-holes.…”
Section: Experimental Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…37 increased further, relatively higher amount of dye leaks out in the fusion time period and hence, relatively higher saturation values are observed. These amphiphilic cations have been shown to induce fusion in egg-PC 24 and DOPC vesicles 23 previously. However, these studies did not comment on the leaky nature of membrane fusion or formation of fusion-holes.…”
Section: Experimental Methodsmentioning
confidence: 76%
“…Eri et al have shown fusion of DMPC+SM (3:1) liposomes under the influence of ionic liquids containing short chain amphiphilic 1-ethyl-3methylimidazolium cations. 23 In another study, Galletti et al have compared the impact of difference cationic head groups on fusion of egg-PC liposomes. 24 Apart from these two reports, ionic liquid induced membrane fusion remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Lipids, disengaged from the disrupted liposomes, have further been shown to aggregate with surface‐active imidazolium based ILs forming IL‐lipid micelles, as seen also with other surfactants . In addition, imidazolium‐ and cholinium‐based ILs with lactate anion and imidazolium, pyrrolidinium, and pyridinium based ILs have been shown to even induce liposome fusion.…”
Section: Introductionmentioning
confidence: 99%
“…The thermo-physical properties of ILs can be tuned by appropriate selection of cation and anion, as a result ILs can be made biocompatible and these are found to be very attractive in various analytical applications, particularly, in the fabrication of various modified electrodeswhichcan be used to extract chemicals or compounds (synthetic colors) from food samples. Reports are available [ 6 12 ]were ILs have been used for the extraction of Sudan and Para Red dyes from chilli powder employinghigh performance liquid chromatography (HPLC), thus showing potential application of ILs in food industries [ 10 11 , 13 15 ].…”
Section: Introductionmentioning
confidence: 99%